PENGARUH PROGRAM PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI KANTOR KEPRESIDENAN REPUBLIK TIMOR LESTE - Boe, Isménia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03.NO.10.TAHUN 2014, 2014)
The purpose of this study was to determine whether training programs simultaneously significant effect on the performance of employees and whether the training program and work motivation partial effect on employee performance. The research was conducted by taking a sample of 64 respondents . Data was collected using a questionnaire that statement. The data analysis technique used is multiple linear regression analysis using SPSS version 15,0 for windows. Based on the results reseach, it is evident that the training program and a significant positive effect on employee performance simultaneously in the office of Presidential of the Republic of East Timor. And that research also have evident proved that the training program and work motivation positive and significant impact on the performance of partially civil servants office of Presidential of the Republic of East Timor. The implication of this study is the employee's performance must be improved, especially in the case; work must comply with the standards, the work must reach the target, the ability to complete the work and attitude of employee cooperation in completing the work. Training programs must be improved in order to increase the ability, change in attitude and behavior change disciplines employees in performing their duties. Motivation should be improved, especially in terms of bonuses, such as the provision of non-bonus promotion, communication and attention superiors to subordinates  in carrying out the work
Keywords: Training Programs, Work Motivation, Employee Performance